2007
DOI: 10.1002/cphc.200700296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Group II Metal Cations on Catecholate Oxidation

Abstract: The unexpected effects of Ca(2+) on the free-radical chain reactions of dopamine, norepinephrine, isoproterenol, and pyrocatechol oxidation are studied using oxygen consumption measurements, EPR-spectroscopy, UV/VIS spectrophotometry, and by potentiometric titration. It is found that the formation of Ca(2+)-catecholate complexes is accompanied by an increase in the dissociation constants (K(ai) ) of their phenolic hydroxyls. At pH>pK(ai) and in the presence of alkaline-earth metal cations, the rate of catechol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…The formation of DPPH 2 was also identified from the peaks of two -NH-at 8.56 and 9.06 ppm, respectively, in CD 3 OD by 1 H-NMR. On the other hand, although pyrCat reduces oxygene O 2 to generate superoxide anion radical (˙O 2 Ϫ ) in one electron transfer pathway, 24) it was found that compounds 5a and b do not generate ˙O 2 Ϫ in 0.1 M KH 2 PO 4 buffer (pH 7.5) (and 90% ethanol) by the chemical luminescence method (data not shown here) (Eq. 4).…”
Section: Resultsmentioning
confidence: 80%
“…The formation of DPPH 2 was also identified from the peaks of two -NH-at 8.56 and 9.06 ppm, respectively, in CD 3 OD by 1 H-NMR. On the other hand, although pyrCat reduces oxygene O 2 to generate superoxide anion radical (˙O 2 Ϫ ) in one electron transfer pathway, 24) it was found that compounds 5a and b do not generate ˙O 2 Ϫ in 0.1 M KH 2 PO 4 buffer (pH 7.5) (and 90% ethanol) by the chemical luminescence method (data not shown here) (Eq. 4).…”
Section: Resultsmentioning
confidence: 80%
“…Catechol forms strong complexes with aluminium and iron (Table 8). Whilst complex formation with calcium ions has not been conclusively demonstrated, their presence leads to modification of the pKa of catechol (in stepwise terms: pKa1 = 9.04; pKa2 = 1.64), indicating that it is likely (Lebedev, Ivanova, Timoshin and Ruuge, 2007). The catecholate ion forms relatively strong complexes with Si.…”
Section: Catecholmentioning
confidence: 99%
“…5 Shift of E r1 and E r2 by metal cation complexation affects semiquinone stability and several accounts show that metal ion can increase the autoxidation rate of catechols. 47,48 It is still of considerable interest to understand the influence of various factors on semiquinone radical stability and electronic structure calculations have been performed. 49,50 Band assignments of vibrational peaks along with ab initio calculation helped elucidate electronic structure of semiquinones as well.…”
mentioning
confidence: 99%